Recent improvements in the management of esophageal anastomotic leak after surgery for cancer. Issue 2 (February 2017) - Messager, M.; Warlaumont, M.; Renaud, F.; Marin, H.; Branche, J.; Piessen, G.; Mariette, C.
Abstract: Anastomotic leakage following total gastrectomy or esophagectomy is a significant complication that considerably increases postoperative mortality. The location of the anastomosis together with the anatomy of the esophagus explains the severity of this complication. Surgical knowledge should include general and specific predictive factors of leakage to avoid any technical-related cause of leakage. Clinical presentations may vary from minimally symptomatic to life-threatening situations. Investigations should be undertaken as soon as the diagnosis is suspected because delay greatly worsens the prognosis. CT scans with oral contrast and low insufflation early endoscopy are the preferred diagnostic tools and can also aid in therapeutic procedures. Communication and multidisciplinary teamwork are the cornerstones of treatment. When the leak occurs early with acute and important sepsis, the recommendation is surgical treatment. On the contrary, if the leak is late, non-symptomatic or minimally symptomatic, conservative management with intensive surveillance could be proposed. When the situation is in between these two extremes, endoscopic treatment is often proposed. Based on a review of the literature and experience from high volume centers, in this educational review, we present the incidence, predictive factors, clinical presentations, diagnostic tools, management, and therapeutic algorithms for anastomotic leaks following elective esophagectomy and total gastrectomy for cancer.